Effect of channel and oxidizer injection slot width on the rotating detonation fueled by pre-combustion cracked kerosene. (December 2019) - Zhong, Yepan; Wu, Yun; Jin, Di; Chen, Xin; Yang, Xingkui; Wang, Shunli
Abstract: In this study, the effect of the channel and oxidizer injection slot width on the rotating detonation fueled by the pre-combustion cracked kerosene was researched. Three channel widths of 15, 25, 40 mm and two slot widths of 0.4, 1 mm were examined in the implemented experiments using cracked kerosene and oxygen-enriched air (oxygen ratio of 30%). The time for the formation of the RDW is extended with the wider channel and shortened with the narrower slot. While the wave speed increases with the increasing channel width, the wave speed is little influenced by the change of the slot width. The lean fuel operating boundary becomes narrower when the channel width increases. The narrower slot tends to increase the occurring probability of the two-counter rotating waves mode while the wider channel has a contrary effect on the rotating detonation. When the flow rate is set at a relatively low level, the acoustic mode may occur near the detonation operating boundary. Highlights: Rotating detonation fueled by pre-combustion cracked kerosene. Wave speed is increased with the wider channel. Narrower oxidizer slot promotes the occur of the two-counter rotating waves mode. Acoustic mode tends to occur at low flow rate near the detonation boundary.